Transient elastography correlated to four different histological fibrosis scores in children with liver disease. - Teufel-Schäfer, Ulrike; Flechtenmacher, Christa; Fichtner, Alexander; Hoffmann, Georg Friedrich; Schenk, Jens Peter; Engelmann, Guido (European Journal of Pediatrics, 2021)
Currently, liver histology is the gold standard for the detection of liver fibrosis. In recent years, new methods such as transient elastography (TE) have been introduced into clinical practice, which allow a non-invasive assessment of liver fibrosis. The aim of the present study was to investigate the predictive value of TE for higher grade fibrosis and whether there is any relevance which histologic score is used for matching. For this purpose, we compared TE with 4 different histologic scores in pediatric patients with hepatopathies. Furthermore, we also determined the aspartate aminotransferase-to-platelet ratio (APRI) score, another non-invasive method, to investigate whether it is equally informative. Therefore, liver fibrosis in 75 children was evaluated by liver biopsy, TE and laboratory values. Liver biopsies were evaluated using four common histological scoring systems (Desmet, Metavir, Ishak and Chevalier's semi-quantitative scoring system). The median age of the patients was 12.3 years. TE showed a good correlation to the degree of fibrosis severity independent of the histological scoring system used. The accuracy of the TE to distinguish between no/minimal fibrosis and severe fibrosis/cirrhosis was good (p = 0.001, AUC-ROCs > 0.81). The optimal cut-off value for the prediction of severe fibrosis was 10.6 kPa. In contrast, the APRI score in our collective showed no correlation to fibrosis.Conclusion: TE shows a good correlation to the histological findings in children with hepatopathy, independent of the used histological scoring system. What is Known: • The current gold standard for detecting liver fibrosis is liver biopsy. Novel non-invasive ultrasound-based methods are introduced to clinical diagnostics. • Most histological scores have been developed and evaluated in adult populations and for only one specific liver disease. What is New: • Transient elastography (TE) in children showed a good correlation to fibrosis severity irrespective of the utilized histological scoring system. • The aspartate aminotransferase-to-platelet ratio (APRI) showed no correlation with different stages of liver fibrosis in children.